Cognitive control under distressing emotional stimulation in adolescents with conduct disorder. Issue 2 (20th September 2013) - Euler, Felix; Sterzer, Philipp; Stadler, Christina
Abstract Aggressive behavior has been linked to deficient processing of emotional stimulation and recent studies indicate that in aggressive juveniles executive functions are impaired when distressing emotional stimulation is being processed. This study examines the interrelation of distressing emotional stimulation and cognitive control in aggressive adolescents and healthy controls. We combined a color‐word Stroop test with pictures from the International Affective Picture System with either neutral or distressing emotional content to assess Stroop interference under neutral and distressing emotional stimulation in 20 male reactive aggressive patients with conduct disorder (CD) and 20 age‐matched male control participants. We found impaired Stroop performance under distressing emotional stimulation in patients compared to healthy controls. No difference was present under neutral emotional stimulation. Our results indicate that cognitive control under distressing emotional stimulation was affected in adolescents with CD but not in healthy controls. We conclude that executive functions in reactive aggressive CD patients are more susceptible to the deleterious effects of distressing emotional stimulation. The results provide a possible explanation for pathologic impulsive‐aggressive behavior under emotional distress in CD patients. Aggr. Behav. 40:109–119, 2014. © 2013 Wiley Periodicals, Inc.